ORTHODONTIC TREATMENT IN PATIENTS WITH HEAD AND NECK IRRADIATION - Martins, Letícia dos Santos Sales; Magalhães, Henrique Souza; Resende, Livia Garcia; Ferreira, Bruno Alves; Dantas, Maria Clara Fernandes Ribeiro; Albertoni, Luigi de Almeida; Cunha, Lara Castor; Rodrigues, Cecília Helpes; Soares, Tamires Elisa de Assis; Chandretti, Paula Carolina de Souza; Fabri, Gisele Maria Campos (Seven Editora, 2026)
Introduction: Orthodontic treatment in patients who have undergone head and neck radiotherapy requires a comprehensive understanding of the biological alterations induced by radiation, including reduced vascularization, impaired bone remodeling, periodontal vulnerability, xerostomia and increased risk of osteoradionecrosis, all of which significantly modify the tissue response to orthodontic forces. Aim: This chapter aims to summarize the major late radiation effects that influence orthodontic planning, define eligibility criteria for intervention, outline necessary biomechanical adaptations and present preventive strategies to minimize treatment-related risks, with additional considerations for pediatric patients who exhibit higher tissue sensitivity and ongoing craniofacial growth. Results: Evidence shows that applying light forces, progressing slowly and maintaining close clinical and radiographic monitoring reduces complications; moreover, meticulous periodontal control, xerostomia management, caregiver guidance and multidisciplinary collaboration are essential to prevent adverse outcomes, particularly osteoradionecrosis. Advances in modern radiotherapy modalities, regenerative approaches and digital technologies have also improved treatment predictability and safety. Conclusion: Orthodontic care after radiotherapy is feasible and safe when based on individualized planning, respect for biological limits and coordinated management among oncology, surgery, periodontics and orthodontics, contributing to stable long-term outcomes and reduced risk of complications.DOI: https://doi.org/10.56238/sevened2026.003-007